The effects of patient-centered task-oriented training on balance activities of daily living and self-efficacy following stroke - Kang, Soon-hee; Choi, Jin-Uk (Journal of Physical Therapy Science, 2015)
[Purpose] This study aimed to determine whether a task-oriented training program improved balance, activities of daily living (ADL) performance, and self-efficacy in stroke patients. Twenty patients with stroke were recruited from a hospital in Cheongju, Korea. [Subjects] Ten of the subjects were assigned to an experimental group that participated in the task-oriented training program, and the other 10 were assigned to a control group that received traditional rehabilitation therapy. [Methods] In the two groups, balance was measured with the Berg Balance Scale (BBS), ADL performance with the Modified Barthel Index (MBI), and self-efficacy with the Self-Efficacy Scale (SES), before and after 4 weeks of training. [Results] Comparative analysis of the experimental group’s pretest and post-test results showed statistically significant differences in the BBS, MBI, and SES scores. There were also significant between-group differences in the BBS, MBI, and SES scores. [Conclusion] The results suggest that a task-oriented training program can be an effective intervention to improve balance ability, ADL performance, and self-efficacy in stroke patients.